2014
DOI: 10.1186/1472-6882-14-469
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and apoptotic activities of alpha-, gamma- and delta-tocotrienol isomers on human cancer cells

Abstract: BackgroundTocotrienols, especially the gamma isomer was discovered to possess cytotoxic effects associated with the induction of apoptosis in numerous cancers. Individual tocotrienol isomers are believed to induce dissimilar apoptotic mechanisms in different cancer types. This study was aimed to compare the cytotoxic potency of alpha-, gamma- and delta-tocotrienols, and to explore their resultant apoptotic mechanisms in human lung adenocarcinoma A549 and glioblastoma U87MG cells which are scarcely researched.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
(62 reference statements)
3
42
0
1
Order By: Relevance
“…The observation that δ-TT is associated with a significant proapoptotic effect in melanoma cells is in agreement with the reported antitumor activity of TTs (mainly δ-TT and γ-TT) in different types of tumors19333544.…”
Section: Discussionsupporting
confidence: 91%
“…The observation that δ-TT is associated with a significant proapoptotic effect in melanoma cells is in agreement with the reported antitumor activity of TTs (mainly δ-TT and γ-TT) in different types of tumors19333544.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies suggest that T3s, which are the unsaturated forms of Vitamin E, are a promising class of anti-cancer compounds that inhibit the growth and survival of many cancer cells—including breast, ovarian, prostate, pancreas, liver, and different skin cancers—without impacting normal cells [7,8,9]. Vitamin E (VE), including T3 analogues, has been shown to be a highly useful compound to encapsulate and enhance the delivery of poorly water-soluble drugs, such as genistein (Gen), quercetin, and other active polyphenols in green tea [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…49 Numerous results from recent studies on tocotrienols also indicated that γ-and δ-tocotrienols exhibited greater anticancer activity than α-or β-tocotrienols, whereas δ-tocotrienol shows a higher efficacy and effectiveness in the induction of apoptosis in both A549 and U87MG cancer cells compared with α-and γ-tocotrienols. 50 Therefore, induction of apoptosis in A549 and H520 cells with be either the result of individual γ-and δ-tocotrienol isomers or their cumulative effects.…”
mentioning
confidence: 99%
“…In lung cancer, the deregulation of the Notch is primarily associated with activating missense mutations mostly in ligand-binding domain (EGF repeats 11 and 12) or the ankyrin domains that lead to a ligand-independent activation. 50 In addition, as a key component of the Notch-mediated transcription complex, Notch can regulate the expression of a number of microRNAs; at the same time, Notch ligands, Notch receptors, or Notch effectors are also subject to regulation by microRNAs. For instance, miR-34a decreased the expression of Notch-1 and its downstream targets, including Hes-1, cyclin D1, Survivin, and Bcl-2, impairing Notch signaling, cell proliferation, and invasion and inducing apoptosis in NSCLC cells.…”
mentioning
confidence: 99%